Effect of pharmacist counselling on patients with type 2 diabetes mellitus in reducing blood sugar levels: a systematic literature review - Rina, Habsyah (International Journal of Basic & Clinical Pharmacology, 2023)
Type 2 diabetes mellitus is one of the most common chronic diseases worldwide, and one approach to managing T2DM is through patient counselling. The aim of this study is to conduct a systematic literature review to identify the impact of pharmacist counselling on patients with T2DM in reducing blood sugar levels. This research utilized the systematic literature review method. Research data were sourced from published literature, retrieved from databases like PubMed and Google Scholar. The collected data were then qualitatively analysed. The results show that, based on 15 journal literatures reviewed, pharmacist counselling in patients with Type 2 Diabetes Mellitus significantly impacts the reduction of blood sugar levels (both glucose and HbA1c levels). The average blood sugar level decreased from 225.69 to 190.98, while another study reported fasting blood glucose levels dropping from 274.5 mg/dl to 239.8 mg/dl. However, there was one study that indicated counselling only managed to slow down the rate of glucose level increase in patients with Type 2 Diabetes Mellitus. Overall, these findings underscore the vital role of pharmacist counselling in the management and control of blood sugar levels in T2DM patients, contributing to better diabetes care and potentially reducing direct medical costs associated with the condition.